2020
DOI: 10.2147/dddt.s249608
|View full text |Cite
|
Sign up to set email alerts
|

<p>Beneficial Effect of Genistein on Diabetes-Induced Brain Damage in the ob/ob Mouse Model</p>

Abstract: Purpose: Diabetes mellitus (DM)-induced brain damage is characterized by cellular, molecular and functional changes. The mechanisms include oxidative stress, neuroinflammation, reduction of neurotrophic factors, insulin resistance, excessive amyloid beta (Aβ) deposition and Tau phosphorylation. Both antidiabetic and neuroprotective effects of the phytoestrogen genistein have been reported. However, the beneficial effect of genistein in brain of the ob/ob mouse model of severe obesity and diabetes remains to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 64 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…Our results demonstrated that genistein or exercise treatment ameliorated the HFHS diet-induced increase in A β content. This effect of genistein on the A β level has been reported in the AD mouse model and the ob/ob mouse model [ 37 , 48 ]. However, to the best of our knowledge, this study was the first to show that genistein reduced the accumulation of A β using a western-style diet consisting of HFHS to induce obesity and T2DM.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Our results demonstrated that genistein or exercise treatment ameliorated the HFHS diet-induced increase in A β content. This effect of genistein on the A β level has been reported in the AD mouse model and the ob/ob mouse model [ 37 , 48 ]. However, to the best of our knowledge, this study was the first to show that genistein reduced the accumulation of A β using a western-style diet consisting of HFHS to induce obesity and T2DM.…”
Section: Discussionsupporting
confidence: 59%
“…Experimentally, genistein has been extensively studied in male and female mice as a promising therapy for the treatment of obesity and diabetes-induced cognitive dysfunction with similar efficacy because of its reported anti-inflammatory, anti-apoptotic, and antioxidant properties [ 32 ]. In addition, we have recently demonstrated a robust neuroprotective effect of genistein in a model of severe obesity [ 37 ]. In fact, four weeks of genistein treatment improved insulin signaling, increased expression of BDNF, and decreased the A β load and hyperphosphorylated tau in the brain of ob/ob mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hipoleptinemic action of GEN was documented in male adult rats, showing a reduction in leptin levels after only three days of treatment with a dose of 5 mg/kg body weight [ 69 ]. In female rats, GEN has no effects on the plasma levels of normal females, but it induces a reduction of serum leptin in pregnant females [ 70 ], as well as in obesity models [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Li et al indicated that genistein has plenty of beneficial effects in diabetes mellitus-induced brain damage [ 66 ]. The authors revealed that this phytoestrogen not only improves brain insulin signaling but also increases neurotrophic support and alleviates AD-related pathologies, such as A β deposition and the level of hyperphosphorylated tau protein.…”
Section: Phytoestrogensmentioning
confidence: 99%